Unequal chances? Inequalities in mortality in Ireland - Katie Duffy; Sheelah Connolly; Anne Nolan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2022)
Life expectancy and mortality are some of the most widely available indicators of population health and are commonly used by governments and international organisations as key indicators of social progress. In addition to being unfair, inequalities in mortality and life expectancy across population groups are a key policy concern as they are potentially avoidable. In this report, data from a variety of sources are used to examine inequalities in mortality in Ireland over the period since 2000, focusing on two broad dimensions of inequality: socio-economic status (SES) (proxied by socio-economic group, which is derived from occupation), and ethnicity/country of birth/nationality. Due to data availability, the analyses of inequalities focus on two key population groups (young infants, and adults). An analysis of emerging patterns in relation to COVID-19 mortality is also undertaken.
Keywords: 330